Flexible Perovskite Solar Cells: Progress and Prospects - Liang, Xiao; Ge, Chuangye; Fang, Qianru; Deng, Wanyuan; Dey, Sukumar; Lin, Haoran; Zhang, Yong; Zhang, Xintao; Zhu, Quanyao; Hu, Hanlin (Frontiers in Materials, 2021)
Flexible perovskite solar cells (FPSCs) have shown great potential in the field of wearable power supply and integration with architectures in the future due to their advantages of high flexibility, light weight, portability, and compatibility with irregular electronic products. As a promising photovoltaic technology compatible with roll-to-roll manufacturing process, FPSCs have made significant progress in the past several years through composition engineering, interface modification, optimization of fabrication process, and exploitation of new charge transport materials. As a result, the light-to-electricity power conversion efficiency of FPSCs has exceeded 20% recently. In this mini review, the latest developments of FPSCs are systematically summarized and discussed, including the flexible substrates and electrodes, as well as the fabrication of high-quality perovskite films. Finally, a prospect on the massive manufacturing of FPSCs as well as the challenge is also discussed.